A Prospective Randomized Trial Comparing Silver Sulfadiazine Cream With a Water-Soluble Polyantimicrobial Gel in Partial-Thickness Burn Wounds. Issue 1 (January 2015) - Black, Jonathan S.; Drake, David B.
Abstract : The lipid base of silver sulfadiazine (SSD) makes removal of the product painful for the patient and difficult for the physician to accurately assess particularly in partial-thickness burn injuries. As an alternative, a water-soluble antimicrobial gel is used at the University of Virginia. We present a prospective, randomized comparison of these two therapies using pain with dressing changes and time to perform dressing changes as our primary endpoints. Adult inpatients with partial-thickness burn wounds were randomized to begin therapy with either SSD cream or the water-soluble burn wound gel (BWG), and then therapies were alternated daily. Pain assessments, time to complete dressing care, total narcotic medication administered, and the number of personnel required for dressing changes were recorded. Eight patients were enrolled resulting in 13 pairs (26 points) of data comparison between the two therapies. Four of the eight enrolled patients (50%) refused to continue receiving SSD because of pain associated with dressing changes and voluntarily withdrew from the study. The amount of time to perform dressing changes was an average of 79 nurse-minutes longer for SSD. A 6.08 greater morphine equivalent was delivered to those having BWG removed. A water-soluble polyantimicrobial gel was superior to SSD in the parameters measured as exhibited by our patient dropout rate and differential time to perform dressing care. Limiting the time to perform dressing care will reduce the cumulative pain experience, improve patient satisfaction, and reduce the resources to deliver care.